2015
DOI: 10.1038/srep13689
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution-and-reduction CVD synthesis of few-layer graphene on ultra-thin nickel film lifted off for mode-locking fiber lasers

Abstract: The in-situ dissolution-and-reduction CVD synthesized few-layer graphene on ultra-thin nickel catalyst film is demonstrated at temperature as low as 550 °C, which can be employed to form transmission-type or reflection-type saturable absorber (SA) for mode-locking the erbium-doped fiber lasers (EDFLs). With transmission-type graphene SA, the EDFL shortens its pulsewidth from 483 to 441 fs and broadens its spectral linewidth from 4.2 to 6.1 nm with enlarging the pumping current from 200 to 900 mA. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The average cross-sectional thickness of the graphene sheets is found to be around 3.2 nm. Figure 3d reveals the existence of 6–8 layers of graphene sheets, considering the thickness of the monolayer graphene is 0.33 nm 67 . A detailed three-dimensional mapping of the PS-FLG nanosheets is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The average cross-sectional thickness of the graphene sheets is found to be around 3.2 nm. Figure 3d reveals the existence of 6–8 layers of graphene sheets, considering the thickness of the monolayer graphene is 0.33 nm 67 . A detailed three-dimensional mapping of the PS-FLG nanosheets is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The five factors in Table 1 are named as A, B, C, D, and E and their levels are coded as mathematical "−1" and "+1" for low and high levels respectively. The two levels of each factors are chosen based on preliminary experimental results and various works reported previously (Nandamuri et al, 2010;Qi et al, 2011;Peng et al, 2013Peng et al, , 2015 which suggested a range of levels for each factor suitable for Graphene synthesis. Since the number of factors involved in the process is 5, the experimental runs as per the Factorial design will be 32 which is quite large to practically experiment with.…”
Section: Design-of-experimentsmentioning
confidence: 99%
“…• C. Therefore, there is a shift in approach and Plasma-Enhanced CVD (PECVD) has become increasingly prominent because of its low operational temperature and has been employed for growing carbon nanostructures successfully (Wu et al, 2002). Nickel substrate has been successfully used for Graphene Synthesis using PECVD (Nandamuri et al, 2010;Qi et al, 2011;Peng et al, 2013Peng et al, , 2015, but the key process parameters and their purview to control and influence the synthesis is not methodically studied. This is necessary as there are more number of growth parameters in PECVD as compared to conventional CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the lift-off process induced by the chemical etching of Ni film was performed at room temperature in the environment of FeCl 3 solution, which was kept as slow as possible to protect the few-layer graphene by greatly diluting the concentration of etching solution (Figure 1). In this way, the few-layer graphene floated on the deionized water surface after the lift-off remains flattened without any corrugation or folded damage before transferring onto the side-polished fiber [23]. The side-polished fiber was dipped into deionized water to scoop up the floated few-layer graphene, which did not risk any damages, as no physical or chemical process was performed at this stage.…”
Section: Methodsmentioning
confidence: 99%